Spatially engineering tri-layer nanofiber dressings featuring asymmetric wettability for wound healing - Tingting Shi; Yuan Liu; Donghui Wang; Dan Xia; Baoe Li; Ruodan Xu; Ning Li; Chunyong Liang; Menglin Chen (Nano Materials Science)
Inspired by the skin structure, an asymmetric wettability tri-layer nanofiber membrane (TNM) consisting of hydrophilic inner layer loaded with lidocaine hydrochloride (LID), hydrophobic middle layer with ciprofloxacin (CIP) and hydrophobic outer layer has been created. The hydrophobic outer layer endows the TNM with waterproof function and anti-adhesion from contaminants. The hydrophobic middle layer with CIP preserves long-term inhibition of bacteria growth and the hydrophilic inner layer with LID possesses optimal water-absorbing capacity and air permeability. The TNM dramatically elevates the water contact angles from 10° (inner layer) to 120° (outer layer), indicating an asymmetric wettability, which could directionally transport wound exudate within the materials and meanwhile maintain a comfortable and moist environment to promote wound healing. Furthermore, the sequential release of LID and CIP could relieve pain rapidly and achieve antibacterial effect in the long run, respectively. In addition, the TNM shows superior biocompatibility towards L929 ​cells. The in vivo results show the TNM could prevent infection, accelerate epithelial regeneration and significantly accelerate wound healing. This study indicates the developed TNM with asymmetrical wettability and synergetic drug release shows great potential as a wound dressing in clinical application.